ELEVATING YOUNG LEARNERS VOCABULARY MASTERY THROUGH KIM’S MEMORY GAME - HAPPY KUSUMA WARDANI; Siti Mukhtarotul Ummah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2023)
This research aims to analyze the implementation of Kim’s memory game to improve the vocabulary mastery of the fifth graders at MI Pembangunan. This research used classroom action research design that included 12 students as the subject of the research. In conducting the research, the researchers collaborated with the classroom English teacher. The researcher and the collaborator worked together in planning, implementing, observing, and reflecting. This research used some instruments such as observation sheets and field notes to observe the implementation of Kim’s memory game during the act of conducting research. The findings showed that the implementation of Kim’s memory game in teaching vocabulary could improve the students’ mastery in vocabulary and encourages them to involve in the teaching learning process. The students’ improvement in vocabulary mastery was reflected on their result of the final test in the second cycle. The mean score of their final test in the second cycle reached to 99,5.